Consumo alimentar e controle glicêmico de diabéticos do ELSA-Brasil - Monteiro, Mayara Freitas (2017)
The prevalence of Diabetes Mellitus has been increasing in Brazil and its treatment is aimed at the glycemic control by the use of medications and behavioral changes through the diet, the physical activities and the adequate body weight. It is recommended the consumption of foods with lower glycemic index and those that promote increased muscle sensitivity to insulin for better metabolic control. Objective: To investigate the association between the alimentary consumption and the glycemic control in diabetics. Method: A cross-sectional study with all ELSABrazil baseline participants using antidiabetic medication. The outcome variable was glycosylated hemoglobin (HbA1C) and the exposure was food consumption evaluated by the amount of consumed nutrients and substances (carbohydrates, proteins, lipids, fibers and alcohol) in quintiles of daily intake. Adjustment variables were sociodemographic conditions, type of antidiabetic medication, nutritional status and physical activity practice. We performed bivariate analysis and logistic regression models. The statistical level of significance of 5% and 95% confidence interval were adopted. Results: From the sample of 1,092 participants, 61% had controlled HbA1C, the most used medication was oral hypoglycemic (86.6%), 82.5% were overweight, 62.2% had inadequate circumference and 96.5% were sedentary. For men, a lower income per capita (OR = 2.656, 95% CI, 1.608-4.389) and the use of insulin (OR = 4.433, 95% CI, 2.011-9.771) were associated with uncontrolled HbA1C. For women, in addition to the lowest per capita income (OR = 2.175, 95% CI, 1.305- 3.624) and isolated insulin use (OR = 6.751, 95% CI, 2.610-17.463), the combined use of medications (OR = 10.10, 95% CI, 4.477-22.784) were associated with uncontrolled HbA1C. Among women, dietary intake was associated with HbA1C and it was showed that the lowest protein (OR = 0.464, 95% CI, 0.251-0.858), lipid (OR = 0.530, 95% CI, 0.282-0.998) and polyunsaturated fats (OR = 0.492, 95% CI, 0.257- 0.940) intake were protective for HbA1C above 7%. Conclusion: Nutritional factors were associated with glycemic control only in diabetic women, and the lower income and the insulin use have increased the chance of diabetics, of both sexes, to present uncontrolled HbA1C.